THE EFFECT OF BIOFERTILIZER FUNGI ON CIHERANG RICE GROWTH AT SOME LEVEL OF SOIL SALINITY - YB. Subowo (The East Java Biological Society, 2013)
research about the effect of fungus contained biofertilizer on Ciherang rice that was growth on different level of soil salinity was conducted. One of the effect of global climate changes is the increase of sea water level. It leads to the expansion of sea water submerged land for agriculture. Salt intrution to the agriculture area considerably decrease soil fertility because of the high salinity. Some of microbes especially soil fungi such as Aspergillus sp and Penicillium sp. are able to grow at high salinity environment. Those fungi were also able to degrade lignocellulose, sollubilize in organic phosphate and provide organic phosphat and produce plant growth hormon especially IAA. Such activities benefit to improve soil fertility in high salinity land as a bio-fertilizer.The objective of this research was to know the growth of rice plant that treated with fungus contained bio-fertilizer on land with different level of salinity. The rice were planted in Green house of Cibinong Science Centre, Cibinong.The research was set up as complete random design with five replication. The rice were watered by 5 conditions: 50% of sea water, 100% of sea water, 100% sea water + 2 % NaCl , fresh water + 5 % NaCl and 100% fresh water as the control. Fertilizer was added to the medium twice. Ten grams of fertilizer were used per polybag (10g/7 Kg), 2 weeks after planting and before flowering subsequently. The observed parameters were plant height, number of tiller, leaves colour, biomass dry weight, soil organic carbon content, cellulosic and lignin degrading activities of the fungus, fungus phosphate-solubilizing potency and fungus production of IAA.The watering treatment lead to 5 level of salinity i.e. : 5,93 dS/m (50% sea water), 9,15 dS/m (100% sea water), 10,42 dS/m (sea water + 2% NaCl), 12,43 dS/m (fresh water + 5% NaCl) and 0,74 dS/m (fresh water). The result showed that among those 5 watering condition, the rice grew best on 5,93 dS/m (watering 50% of sea water). This result was considered as the best since the plant height and number of tiller were not significantly different with those of the control. Plants height and number of tiller were 74,4 cm and 11 respectively. On the higher salinity level the plant growth was inhibited. The ability of rice to withstand the high salinity possibly was supported by the fungus activities of providing organic phosphate and IAA growth substance.